2018
DOI: 10.1590/0004-282x20170179
|View full text |Cite
|
Sign up to set email alerts
|

Non-inflammatory cerebrospinal fluid delays the diagnosis and start of immunotherapy in anti-NMDAR encephalitis

Abstract: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a form of autoimmune encephalopathy that presents with a wide variety of symptoms, including neuropsychiatric manifestations. The authors’ aim for this study was to analyze the results of paraclinical studies of patients with a diagnosis of anti-NMDAR encephalitis and the association between symptom onset and diagnosis, and start of immunotherapy. Retrospective data of 29 patients with anti-NMDAR encephalitis were gathered and analyzed. Abnormal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
3
8
0
1
Order By: Relevance
“…In addition, in the present study more than a third of patients with anti-NMDAR encephalitis did not exhibit pleocytosis via routine CSF examination. This result is concordant with a previously reported case series in which initial non-inflammatory CSF varied widely in 15%-96% of patients at the first evaluation [9]. It is notable that initial noninflammatory CSF evidently does not exclude a diagnosis of anti-NMDAR encephalitis, and in the past some patients may have been misdiagnosed leading to delays in the initiation of immunotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in the present study more than a third of patients with anti-NMDAR encephalitis did not exhibit pleocytosis via routine CSF examination. This result is concordant with a previously reported case series in which initial non-inflammatory CSF varied widely in 15%-96% of patients at the first evaluation [9]. It is notable that initial noninflammatory CSF evidently does not exclude a diagnosis of anti-NMDAR encephalitis, and in the past some patients may have been misdiagnosed leading to delays in the initiation of immunotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…The most common antibody found in our study was anti-NMDAR, as reported in other series of AE patients (13). A recent study of 29 cases of anti-NMDAR encephalitis reported an absence of inflammatory markers in CSF in almost 50% of patients, and a delayed time to diagnosis in these cases (14). In our study, time to diagnosis was similar in anti-NMDAR encephalitis patients regardless of their inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…2 In previous reports, initial non-inflammatory CSF were noted in 15%-96% of the patients. 3 EEG could be a diagnostic aid, given that in most case series, it was abnormal in more than 90% of the cases. 4 But findings were usually non-specific.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…5 The absence of CSF pleocytosis and/or increased proteins are known to delay diagnosis, as well as the length of time to initiate immunotherapy in patients with anti-NMDA encephalitis. 3 Additionally, EEG and MRI could be a diagnostic aid, but the absence of abnormality of them does not exclude anti-NMDAR encephalitis. In conclusion, follow up tests with close observation may be considered in patients with the atypical psychiatric symptoms, although there are initially no significant abnormal findings on CSF, MRI, and EEG.…”
Section: Conflict Of Interestmentioning
confidence: 99%